Bacterial Energetic Requirements for Helicobacter pylori Cag Type IV Secretion System-Dependent Alterations in Gastric Epithelial Cells - Lin, Aung Soe (Infect Immun, 2020)
Helicobacter pylori colonizes the stomach in about half of the world’s population. H. pylori strains containing the cag pathogenicity island (cag PAI) are associated with a higher risk of gastric adenocarcinoma or peptic ulcer disease than cag PAI-negative strains. The cag PAI encodes a type IV secretion system (T4SS) that mediates delivery of the CagA effector protein as well as nonprotein bacterial constituents into gastric epithelial cells. H. pylori-induced nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activation and interleukin-8 (IL-8) secretion are attributed to T4SS-dependent delivery of lipopolysaccharide metabolites and peptidoglycan into host cells, and Toll-like receptor 9 (TLR9) activation is attributed to delivery of bacterial DNA. In this study, we analyzed the bacterial energetic requirements associated with these cellular alterations. Mutant strains lacking Cagα, Cagβ, or CagE (putative ATPases corresponding to VirB11, VirD4, and VirB4 in prototypical T4SSs) were capable of T4SS core complex assembly but defective in CagA translocation into host cells. Thus, the three Cag ATPases are not functionally redundant. Cagα and CagE were required for H. pylori-induced NF-κB activation, IL-8 secretion, and TLR9 activation, but Cagβ was dispensable for these responses. We identified putative ATP-binding motifs (Walker-A and Walker-B) in each of the ATPases and generated mutant strains in which these motifs were altered. Each of the Walker box mutant strains exhibited properties identical to those of the corresponding deletion mutant strains. These data suggest that Cag T4SS-dependent delivery of nonprotein bacterial constituents into host cells occurs through mechanisms different from those used for recruitment and delivery of CagA into host cells.